Almacenamiento de material de siembra de yuca en la Costa Atlantica - López, J. (International Center for Tropical Agriculture, 1990)
Four on-farm trials were established in Cordoba and Sucre, Colombia, to assess different storage methods using the regional cassava var. Venezolana (M Col 2215). Three treatments were common to all expt.: the 1st was use of fresh seed (unstored). The 2nd consisted in branches grouped in bunches of 30 units, immersed for 5 min in a solution of 3 g benomyl, 3 g captan, and 2 cc aldrin/l water and then stored outdoors in vertical position on soil dug up so that the branches were buried 5 cm. A ditch around the branches helped retain irrigation water. The 3rd treatment was similar to the 2nd, but no chemical treatment was applied. The duration of storage varied among the different expt. (103, 75, 80, and 110 days). Other variables were also assessed such as origin of stems and horizontal vs. vertical placement. Results indicated that it is feasible to store cassava branches for approx. 3 mo. and obtain acceptable planting material. Vertical storage was preferable to horizontal storage since both the loss of planting material and the wt. reduction of usable cuttings were lower. Overall, vertical storage caused a 20 percent decrease in usable planting material and a 10 percent decrease in the wt. of cuttings selected as usable. With vertical storage, corresponding reductions were 31 and 35 percent. No differences were observed in the suitability for storage of planting material obtained in monoculture or in associated cropping. Chemical treatment was considered a preventive measure that helped avoid seed deterioration under unfavorable storage conditions. (CIAT)